PENERAPAN LAYANAN BK BERBASIS PENDIDIKAN KARAKTER UNTUK MENCEGAH KECENDERUNGAN PENYALAHGUNAAN NARKOBA DI SMK NEGERI 5 MAKASSAR - Hasbahuddin Hasbahuddin (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
The study aims at (1) discovering the tendency of drugs abuse before and after counseling service based on character education is given to student at SMKN 5 Makassar, (2) examining whether there is influence of counseling services based on character education to prevent drugs abuse to student at SMKN 5 Makassar? The study employed quantitative approach with true experiment. The research design was pretest-posttest control group design. The population of the study was 110 students and the samples were 60 students which chosen by employing purposive sampling technique. The result of the study revealed that (1) the pretest result of tendency of drugs abuse of students before counseling services based on character education was given, both for the experiment group and the control group in general were in high category. After the treatment was given, the result of posttest to the experiment group is in low category, whereas the control group which did not receive the treatment based on character education but received the treatment from counselor in school is in high category, (2) there are significant differences between students who received counseling services based on character education from the ones who received counseling services by the school’s counselor to prevent drugs abuse of students at SMKN 5 Makassar